2015
DOI: 10.2174/1874306401408010085
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Corticosteroids and Bone Health

Abstract: Inhaled corticosteroids (ICS) are the cornerstones in the management of bronchial asthma and some cases of chronic obstructive pulmonary disease. Although ICS are claimed to have low side effect profiles, at high doses they can cause systemic adverse effects including bone diseases such as osteopenia, osteoporosis and osteonecrosis. Corticosteroids have detrimental effects on function and survival of osteoblasts and osteocytes, and with the prolongation of osteoclast survival, induce metabolic bone disease. Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 74 publications
0
25
0
1
Order By: Relevance
“…Corticosteroids have detrimental effects on function and survival of osteoblasts and osteocytes, and with the prolongation of osteoclast survival, induce metabolic bone disease 17 . Inhaled corticosteroids are widely accepted for their potent anti-inflammatory effects in the lungs and low systemic activity 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Corticosteroids have detrimental effects on function and survival of osteoblasts and osteocytes, and with the prolongation of osteoclast survival, induce metabolic bone disease 17 . Inhaled corticosteroids are widely accepted for their potent anti-inflammatory effects in the lungs and low systemic activity 18 .…”
Section: Introductionmentioning
confidence: 99%
“…FEV1%Pre and the bone density of lumbar vertebra and the bone density of femoral neck are significantly and positively correlated. However, some research has not found the correlation between the decrease of bone mineral density and the airflow obstruction [25]. In conclusion, there are various factors related to osteoporosis secondary to COPD.…”
Section: Discussionmentioning
confidence: 84%
“…Corticoids have damaging effects on the function and survival of osteoblasts and osteocytes, and on the maintenance or prolonging of the lifespan of osteoclasts that are associated with metabolic bone diseases. Osteoporosis caused by corticosteroids is associated with some abnormalities such as fracture of the vertebrae of the spine and femoral neck [26]. Glucocorticoids reduce the process of osteoblastogenesis, increase osteoblasts' cell death, and reduce their ability of bone formation [27].…”
Section: Discussionmentioning
confidence: 99%